ImpediSense:A long lasting wireless wearable bio-impedance sensor node - Dheman, Kanika; Mayer, Philipp; Eggimann, Manuel; Schuerle, Simone; Magno, Michele (Sustainable computing informatics and systems, 2021)
•Design and implementation of an energy efficient wearable bio-impedance sensor node for compact footprint (with dimensions 3 cm × 1.8 cm × 0.6 cm) and small size battery.•Design optimisations and implementation for low power and high accuracy bio-impedance front-end in tetrapolar electrode configuration.•Experimental evaluation of sensor node accuracy and precision when measuring impedimetric loads with the implemented low power design.•The estimation and compariosn of theoretical and experimental measures of battery life using a small form factor Li-Ion battery. Bio-impedance is a method to assess the body composition safely, non-invasively and inexpensively. This method finds application for assessing body fluid and body composition for multiple disease scenarios in clinical environments and for at-home monitoring of chronic ailments. Bio-impedance sensors require higher power than most other bio-signal acquisition systems due to need of high frequency current and voltage management. Currently used bio-impedance devices are bulky due to incorporation of large batteries and cannot be used for long term monitoring, especially for wearable applications. This limits the widespread implementation of bio-impedance measurement devices. We present the design and implementation of a wireless wearable bio-impedance sensor node, ImpediSense, which has a low power system design that achieves long duration operability without compromising on sensor measurement accuracy and precision. Experimental evaluation show a battery life of several months for measuring bio-impedance with power duty cycling every 1 min over ten frequencies in the range of 10 kHz–100 kHz, using a small form factor 250 mA h Li-ion battery. The lifetime is achieved due to several power optimization implemented in system design of hardware and firmware resulting in active power of 53 mW and idle power of 15.7 μW. Additionally, the presented sensor node shows high performance in terms of accuracy of impedance measurement with an error less than 1.5 % and precision of 0.6 Ω when measuring tetrapolar bio-impedance of the human body. With the inclusion of a small sized battery, ImpediSense has a compact form factor with dimensions 3 cm × 1.8 cm × 0.6 cm, making it more conducive for incorporation in wearable systems.